Vaginal-assisted laparoscopic sacrohysteropexy and vaginal hysterectomy with vaginal vault suspension for advanced uterine prolapse: 12-month preliminary results of a randomized controlled study - Huseyin Cengiz; Sukru Yildiz; Ismail Alay; Cihan Kaya; Ecem Eren; Derya Ece Iliman (Wolters Kluwer Medknow Publications, 2021)
Objective: Vaginal-assisted laparoscopic sacrohysteropexy (VALH) is a new modified form of uterine-sparing prolapse surgery using a combined vaginal and laparoscopic approach. We aimed to compare 1 year efficacy and safety of VALH and vaginal hysterectomy + vaginal vault suspension (VH + VVS) in the surgical treatment of apical pelvic organ prolapse (POP). Materials and Methods: Women who requested surgical treatment for stage 2-4 symptomatic uterine prolapse were recommended to participate in one year-long randomized study between July 2017 and January 2019. POP Quantification (POP-Q) examination and validated questionnaires such as International Consultation on Incontinence Questionnaire Vaginal Symptoms (IVIQ-VS) survey, Urogenital Distress Inventory (UDI-6), Incontinence Impact Questionnaire Short Form (IIQ-7), and Patient Global Impression of Improvement (PGI-I) were recorded at baseline and 12 months after surgery. The main primary outcome measure was apical prolapse recurrence. Secondary results were duration of surgery, pain score, blood loss, postoperative hospital stay, and quality of life scores related to prolapse. Results: There were 15 women in VALH and 19 women in the VH + VVS group. ICIQ-VS score, ICIQ-QOL, UDI-6, and IIQ-7 scores were improved for both groups. According to the PGI-I scores, 80% of subjects in the VALH group, and 100% in the VH + VVS group, were "very much better" or "much better" with their prolapse symptoms at their 1-year follow-up. There was no reoperation or operation-related complication in both groups. Conclusion: VALH and VH + VVS have similar 1-year cure rates and patient satisfaction.